A sporting chance - Brown, Sherrod; Garvey, Timothy; Harden, Troy (Groupwork, 2012)
This paper assesses the relevance of social work group methods with athletics and sports programming in urban settings. Exploring the connection between sports teams, sports-related interventions, and groupwork, the authors offer a conceptualization for approaching group interventions utilizing sports, as well as sports teams incorporating social work group principles. Social workers are well-suited to support these types of endeavors, as social work as a profession seeks to work with underserved populations, provide an ethical barometer to professional approaches to well-being, and have multiple methods of addressing social and emotional concerns.